Peran Sektor Jasa terhadap Perekonomian DKI Jakarta: Analisis Input-Output - Hartono, Djoni (Jurnal Ekonomi dan Pembangunan Indonesia, 2003)
During the development of any economies, the structural transormation will put the services sector to yield higher role while leaving the primary and other goods sector in diminishing share. Using Input-Output model, we analyse the possibilities of making OKI Jakarta as services town. Based on total forward, total backward linkage and other analysis output, we conform the highest role of services sector in this province. We also find that the final demand for services sector is higher than its intermediate demand, showing this product of this sector is mainly used for direct consumption.